IMPLEMENTATION OF PROBLEM BASED LEARING METHODS TO INCREASE LEARNING OUTCOMES OF CREATIVE PRODUCTS AND ENTREPRENEURSHIP AT MATERIALS OF COST OF PRODUCTION IN CLASS XI OF LIGHT VEHICLE ENGINEERING SMK NEGERI 1 MERDEKA FOR THE 2020/2021 ACADEMIC YEAR 2020/2021 - Tarigan, Rinawati Br (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
The problem of this research is the low learning outcomes (Creative Products and Entrepreneurship) of PKK on the material cost of production in class XI of SMK Negeri 1 Merdeka, Merdeka sub-district, Karo Regency, from 26 students, 45% completed. The aim is to improve student learning outcomes in PKK subjects on the material on the cost of production material in class XI of SMK Negeri 1 Merdeka by applying the problem based learning method. The type of research used is Classroom Action Research with 2 cycles, each cycle consisting of stages of planning, implementation, observation and reflection. Data collection techniques used are observation and learning outcomes tests at the end of each cycle, data collection tools are carried out using observation guide sheets and test questions. The data analysis technique used is qualitative and quantitative analysis. The results of the study can be stated that in the first cycle of the cognitive domain the average value of the pretest is 47.72 posttest, the percentage is 63.6%, which means that from 26 students only 11 were able to achieve the KKM score. The results of the affective domain are 63%, the average value is 69.09, while the psychomotor domain is 63% with an average value of 71.81. The first cycle N-gain score was 0.427 in the medium category. In the second cycle the average value of the pretest was 62.72 posttest 80 with a percentage of 82%. The second cycle N-gain score was 0.486 in the medium category, the teacher's performance was 83.6 in the very good category, the affective average was 81.8, 82%, the psychomotor average was 82.7, with 82%. So it means that there is an increase in student learning outcomes from the first cycle with a score of 0.427 in the second cycle to 0.486 with 82% completeness.